2011
DOI: 10.1016/j.archger.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depression and their relationship with health status and social service use

Abstract: This longitudinal study was conducted between 1994 and 2004 in a cohort of Southern Taiwan communityliving elderly residents. The study aims to explore the trajectories of depression and how these patterns differed between respondents who survived and those who died during data collection phases; this study also investigated how health status change and health/social service use predicted the different trajectories of depression. Eight hundred and ten participants had completed all six waves of the survey or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
20
1
1
Order By: Relevance
“…In contrast with the current depressive symptoms outcome, accumulating evidence from other studies shows that for most adults, depressive symptoms are relatively stable following middle age (Montagnier et al, 2014;Musliner, Munk-Olsen, Eaton, & Zandi, 2016). We note that individual differences in age-related trajectories of depressive symptoms are largely attributed to the presence/absence of chronic disease and physical impairment (Chen et al, 2011;Musliner et al, 2016). SHARE data includes a single measure to track the number of chronic diseases and multiple measures of functional capacity (e.g., grip strength, difficulties in daily activities).…”
Section: Discussioncontrasting
confidence: 70%
“…In contrast with the current depressive symptoms outcome, accumulating evidence from other studies shows that for most adults, depressive symptoms are relatively stable following middle age (Montagnier et al, 2014;Musliner, Munk-Olsen, Eaton, & Zandi, 2016). We note that individual differences in age-related trajectories of depressive symptoms are largely attributed to the presence/absence of chronic disease and physical impairment (Chen et al, 2011;Musliner et al, 2016). SHARE data includes a single measure to track the number of chronic diseases and multiple measures of functional capacity (e.g., grip strength, difficulties in daily activities).…”
Section: Discussioncontrasting
confidence: 70%
“…Studies conducted in Taiwan in 1994 – 2004 showed that people aged 65 or older are more likely to suffer from depression than younger ones. In 1994 the percentage of people in this age group was 16.3%, but 10 years later it was 29.9% [49]. Moreover, in people with chronic diseases, depression symptoms are observed more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Most existing studies of depression among the older people are cross-sectional. Although a few longitudinal studies examined the change of depressive symptoms for older adults over time (Taylor & Lynch, 2004;Yang & George, 2005;Koenig et al, 2006;Andreescu et al, 2008;Cui et al, 2008;Taylor et al, 2008;Chiao et al, 2009, Hsu, 2009Capioppo et al, 2010;Chen et al, 2010;Tomey et al, 2010;Brault et al, 2011;Franz et al, 2011;Kamen et al, 2011;Rapp et al, 2011), most studies were conducted in Western developed nations. In addition, the heterogeneity of depressive symptoms over time is little explored in the existing literature.…”
Section: Introductionmentioning
confidence: 99%